The Effect of Iba and Cutting Diameter on Inducing Roots of Cotinus Coggygria Scop. and Rhus Coriaria L. (Anacardiaceae) - Muhamed, Hassan N.; Dawod, Nasser A. (Science Journal of University of Zakho, 2017)
Because of the difficulty in their vegetative propagation, both Rhus coriaria L. and Cotinus coggygria Scop. (Ancardaceae) are rarely introduced into the forest nursery trade. Vegetative propagation is practiced in forestry to produce seedlings of desired genetic properties within a short period and when seeds displaying a status of complex dormancy. In the present study, the possibility of the multiplication by stem cuttings was studied for Sumac, the high ethnobotanical shrub value and for Cotinus, the endangered shrub, to give more insight into their propagation technique. Between January-July 2014, using complete randomized block design (C.R.B.D) in four replicates, we evaluated the effectiveness of applying four different Indole-3-Butyric Acid (IBA) concentration to two stems cutting diameters in producing C. coggygria and R. coriaria. However, the former species due to the poor survival percentage (lower 5%) excluded from the analysis. Optimum results of C. coggygria were obtained with IBA 20000 mg.l -1 and cutting diameter more than 1 cm. (rooting % 60, number of roots 17.33, number of branches 3.75 and the number of leaves 19.33 while nonsignificant increase was recorded in root length. 16.33 cm.). The results indicated that Cotinus is relatively easy to propagate by stem cutting in comparing with Sumac with rootability increases significantly with increasing of IBA concentration and stem cutting diameter. Further studies are needed for more reasonable rooting results to meet the large quantity demand of elite seedling material that could be later used to restore the natural populations of C. coggygria and R. coriaria.